The Ability in Converting Verbal Information into Non-Verbal Information in Grade XI Students of SMKN 4 Padang Sidimpuan - Muhammad Hamzah Fansuri Hasibuan; Sisi Rosida (ITScience (Information Technology and Science), 2021)
Abstract Verbal and non-verbal communication plays a vital role in delivering messages. Therefore, this study examines the level of students’ ability to convert oral information into non-oral information. The type of this study was quantitative research using a descriptive method. The population was all students in SMKN 4 Padangsidimpuan, while the samples were grade XI students of SMKN 4 Padang Sidimpuan, totaling 75 students. The applied data analysis techniques were tests and documentation. The results of student learning outcomes showed a mean value of 89.67, indicating that students could convert verbal information into non-verbal information, as evidenced by the percentage of students’ abilities in the “capable” category greater than that of students in the “incapable” class. The percentage of students in the capable category was 77.14%, while students in the incapable class were 30%.